2006
DOI: 10.2478/s11534-006-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of time resonance (explosion) phenomena in high-energy nuclear reactions

Abstract: This study shows that the exponential decrease of the energy spectra, accompanied by slight oscillations, with final-fragment energy in high-energy nuclear reaction, and independent of fragments, targets, projectiles, and projectile energies, can be explained under some conditions in the range of strongly overlapping compound resonances by a new phenomenon of time resonances (explosions). These time resonances (explosions) correspond to the formation of a few highlyexcited, non-exponentially decaying nuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…(Olkhovsky, 1984;1990;1992;1998); as well as of new phenomena, about time delays-advances in nuclear physics and about time resonances or explosions of highly excited compound nuclei, in Refs. (D'Arrigo et al, 1992;Olkhovsky et al, 2006). Let us also recall that, besides the time operator, other quantities, to which (maximal) hermitian operators correspond, can be analogously regarded as quantum-physical observables: For example, von Neumann himself (Recami, 1976;Von Neumann, 1955)) considered the case of the momentum operator −i∂/∂x in a semi-space with a rigid wall orthogonal to the x-axis at x = 0, or of the radial momentum −i∂/∂r, even if both act on packets defined only over the positive x or r axis, respectively.…”
Section: Some Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Olkhovsky, 1984;1990;1992;1998); as well as of new phenomena, about time delays-advances in nuclear physics and about time resonances or explosions of highly excited compound nuclei, in Refs. (D'Arrigo et al, 1992;Olkhovsky et al, 2006). Let us also recall that, besides the time operator, other quantities, to which (maximal) hermitian operators correspond, can be analogously regarded as quantum-physical observables: For example, von Neumann himself (Recami, 1976;Von Neumann, 1955)) considered the case of the momentum operator −i∂/∂x in a semi-space with a rigid wall orthogonal to the x-axis at x = 0, or of the radial momentum −i∂/∂r, even if both act on packets defined only over the positive x or r axis, respectively.…”
Section: Some Conclusionmentioning
confidence: 99%
“…4. Section 4 has been devoted to the association of unstable states (decaying "resonances") with the eigenvectors of quasi-hermitian (Agodi et al, 1973;Olkhovsky et al, 2006;Recami et al, 1983) Hamiltonians. 5.…”
Section: Some Conclusionmentioning
confidence: 99%
“…The theoretic origin of the earlier revealed phenomena "time resonances (explosions)" rises either from the strict self-consistent time analysis of the compound nuclei or clots at the range of strongly overlapped energy resonances (see [1]), or, in an alternative way, from the qualitative analysis of eigen values of the time operator T defined by appropriate complex values of the compound-nucleus Hamiltonian H through the commutation relation [H T ] = (see [2]). …”
Section: Introductionmentioning
confidence: 99%
“…[1] by "time resonance (or explosion)". In the previous above-mentioned paper [1] it was shown that the reaction amplitude αβ can have a more general form like…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation